Pengaruh Financial Literacy dan Financial Attitude terhadap Financial Management Behavior Mahasiswa melalui Financial Self-Efficacy - Ashar Basyir; Ary Natalina; Dyah Palupi; Istichanah Istichanah; Noor Muhammad Adipati (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of Financial Literacy and Financial Attitude on students' Financial Management Behavior with Financial Self-Efficacy serving as an intervening variable. The study is motivated by the relatively low quality of students' financial management behavior despite the increasing accessibility of digital financial services, highlighting the need to better understand the factors influencing such behavior. This research employed a quantitative approach with an explanatory research design. The study population consisted of university students in Indonesia, with a sample of 300 respondents determined using the Lemeshow formula and selected through purposive sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method through the SmartPLS application. The findings indicate that Financial Literacy has a positive and significant effect on Financial Self-Efficacy (t = 7.254 > 1.96) and Financial Management Behavior (t = 4.132 > 1.96). Furthermore, Financial Attitude positively and significantly influences Financial Self-Efficacy (t = 6.118 > 1.96) and Financial Management Behavior (t = 3.584 > 1.96). In addition, Financial Self-Efficacy has a positive and significant effect on Financial Management Behavior (t = 8.261 > 1.96). The mediation analysis further reveals that Financial Self-Efficacy significantly mediates the relationship between Financial Literacy (t = 5.481 > 1.96) and Financial Attitude (t = 4.976 > 1.96) on Financial Management Behavior. The contribution of this study lies in demonstrating that Financial Self-Efficacy functions as a psychological mechanism that bridges the effects of Financial Literacy and Financial Attitude on Financial Management Behavior. These findings are expected to provide valuable insights for higher education institutions in designing financial education programs that not only enhance students' financial knowledge and attitudes but also strengthen their confidence in managing personal finances effectively.